A Comparative Study of Long‐Term Effects on Fire‐Affected Volcanic Soils in Two Different Ecosystems in the Canary Islands. (2nd December 2015) - Mora, Juan Luis; Armas‐Herrera, Cecilia M.; Guerra, José Asterio; Arbelo, Carmen D.; Rodríguez‐Rodríguez, Antonio; Notario del Pino, Jesús S.
Abstract: Volcanic soils have unique properties that can be specifically affected by fire. In this work, we use a chronosequence approach to investigate the long‐term effects of wildfires on the surface and topsoil (0–30 cm) of volcanic soils in two different ecosystems: the Canary pine forest (dry and fire‐adapted) and the laurel forest or monteverde (subhumid and not prone to fire). Redundancy analysis and partial Kendall's correlation were used to analyse the relationship between soil characteristics and the wildfire chronosequences, controlling most significant environmental variables. No long‐term effects of fire were observed on the pine forest topsoil, but strongly persistent erosion‐related features were found on the soil surface, suggesting that chronic erosion might occur as a result of increased wildfire frequency. The soils of the monteverde were affected over the long term by severe losses of organic matter including highly humified and complexed forms. Organic losses appeared to be mainly due to erosion and associated with decreases in water‐holding capacity and in the levels of organo‐complexed metals and bioavailable nutrients such as boron or zinc. Fire also led to decreased bioavailability of some nutrients (e.g. phosphorus) and increased release of other elements (e.g. silicon), most likely by exposing surfaces of short‐range‐order minerals. Better management is needed to reduce irreversible effects of severe wildfires on these soils. Copyright © 2015 John Wiley & Sons, Ltd.